Correlation between viruses and bacteria in coral mucus at Cat Ba and Long Chau areas, Vietnam - Thu, Pham The (Academia Journal of Biology, 2015)
Bacteria have an important role in the coral health, but is less studied. In order to clarify the question mentioned above, this paper is focusing on the correlation between the viral abundance and bacterial community characteristics (abundance, genetic diversity, activity) in the mucus of 12 coral species distribution in the Cat Ba and Long Chau areas, Hai Phong. The results showed that the viral abundance was positive correlation with bacterial abundance (R=0.500; p=0.041) and was negative correlation with the characteristics of respiration (R=-0.611; p=0.009), the organic matter absorption (R=-0.522; p=0.032) of microbial communities. Therefore, the role of viruses related to the coral health was shown by the role controlling bacterial abundance and activity of bacterial communities living on coral.